Global Cultural Economy and Capital Involvement: A Case Study of the Production of the Television Series Game of Thrones - Afina, Berliana Azka (Universitas Padjadjaran, 2026)
This article examines how global capital structures shape the production and worldwide circulation of Game of Thrones within the contemporary global cultural economy. Drawing on Arjun Appadurai’s framework, the study addresses a central problem in global media capitalism: structural inequality between core and peripheral actors in the distribution of economic benefits and symbolic power. Using a qualitative critical interpretive approach, the analysis explores how financial power coordinates media infrastructures, production technologies, creative labor mobility, and ideological circulation. The findings show that financial dominance constitutes the primary organizing force in the global production of Game of Thrones. Transnational capital controlled by HBO and WarnerMedia enables centralized control over production, digital distribution, and creative labor, positioning peripheral countries mainly as consumption markets rather than equal cultural producers. Furthermore, the global circulation of the series normalizes Eurocentrist narrative framing and symbolic representation. This article contributes to International Relations by demonstrating how popular culture functions as an instrument of soft power within global media capitalism and advances the political economy of culture by illustrating how financial dominance reproduces center– periphery inequality. Artikel ini menganalisis bagaimana struktur kapital global membentuk proses produksi dan sirkulasi global serial televisi Game of Thrones dalam konteks ekonomi budaya global kontemporer. Dengan menggunakan kerangka pemikiran Arjun Appadurai, penelitian ini menyoroti persoalan utama dalam kapitalisme media global, yaitu ketimpangan struktural antara aktor pusat dan periferi dalam distribusi manfaat ekonomi serta kekuasaan simbolik. Melalui pendekatan kualitatif dengan analisis interpretatif kritis, kajian ini mengeksplorasi bagaimana kekuatan finansial mengoordinasikan infrastruktur media, teknologi produksi, mobilitas tenaga kerja kreatif, serta sirkulasi ideologis. Hasil penelitian menunjukkan bahwa dominasi finansial merupakan kekuatan pengorganisasi utama dalam produksi global Game of Thrones. Kapital transnasional yang dikendalikan oleh HBO dan WarnerMedia memungkinkan kontrol terpusat atas produksi, distribusi digital, dan tenaga kreatif, sehingga menempatkan negara-negara periferi terutama sebagai pasar konsumsi alih-alih sebagai produsen budaya yang setara. Lebih jauh, sirkulasi global serial ini menormalkan kerangka naratif dan representasi simbolik yang bersifat Eurosentris. Artikel ini berkontribusi pada kajian Hubungan Internasional dengan menunjukkan bagaimana budaya populer berfungsi sebagai instrumen soft power dalam kapitalisme media global, serta memperkaya ekonomi politik budaya melalui analisis tentang bagaimana dominasi finansial mereproduksi ketimpangan relasi pusat–periferi.